Evaluation of the impact of managerial factors on the sustainability of the poverty alleviation egg laying project in the Vhembe District, South Africa - Tshikosi, Shumani Joseph (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Animal Sciences. Livestock Management))--University of Stellenbosch, 2009.